Fewpal
+4 votes
867 views
in Mathematics by (64.1k points)
edited by
If the sum of first p terms of an A.P. is equal to the sum of the first q terms, then find the sum of the first (p + q) terms.

1 Answer

+7 votes
by (13.5k points)
selected by
 
Best answer

Solution: we have given

Sp=Sq

p/2[2a +(p-1)d]=q/2 [2a+(q-1)d]

p[2a +pd - d]=q[2a+qd - d ]

2ap + p2d - pd =2aq + q2d -qd

2ap-2aq +p2d -q2d -pd +qd =0

2a (p-q) +(p+q)(p-q)d -d(p-q)=0

(p-q)[2a + (p+q)d - d ]=0

2a + (p+q)d - d=0

2a + [(p+q)-1]d=0

Multiply both sides with (p + q)/2

by (12 points)
2a + [(p+q)-1]d=0
How did (1) came?
by (25.4k points)
@Shabbir  2a + (p+q)d - d=0 taking d as common from the equation we will get

2a + [(p+q)-1]d=0

Everything is elaborated in the question, I hope it helps you

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...